Tooth supported overdenture: Case report - Quan, Pham Nguyen (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
Objective: Preserving the natural tooth root in prosthetic treatment improves the support, retention and stability of the restoration. The concept of tooth supported overdenture with attachments is based on a reduction in the root/crown ratio and a combination of retention on a custom attachment to improve retention for the denture. The aim of this case report is to present the clinical steps to perform tooth supported overdenture with cast attachment in patients with large maxillary torus. Methods: A 60-year-old female patient came to the clinic because her old denture cannot be used due to loose abutment teeth. The patient has a large maxillary torus extending to the vibration line. The final treatment plan is to extract the hopeless loose teeth and use the remain maxillary roots to serve as abutment teeth for the new removable partial denture. The sequence of treatment after periodontal and endodontic treatments is preparation of post space, taking impression and cast post with attached male part. The steps of fabricating removable dentures are performed simultanously with the post fabrication to save time for the patient. Female part of the attachment (Kugel hook) is mounted on the male part of the post and clinical pick up of attachment dental is performed chairside using to the self curing dental acrylic. Conclusion: The incorporation of attachment into the tooth supported overdenture improves the support, retention and stability of the restoration and slows down the bone resorption process. This is one of the goals of preventive prosthodontics.